Phosphofructokinase and Malate Dehydrogenase Participate in the In Vitro Maturation of Porcine Oocytes. Issue 6 (11th October 2014) - Breininger, E; Vecchi Galenda, BE; Alvarez, GM; Gutnisky, C; Cetica, PD
Contents Oocyte maturation depends on the metabolic activity of cumulus–oocyte complex (COC) that performs nutritive and regulatory functions during this process. In this work, the enzymes [phosphofructokinase (PFK) and malate dehydrogenase (MDH)] were tested to elucidate the metabolic profile of porcine COCs during the in vitro maturation (IVM). Enzymatic activity was expressed in U/COC and U/mg protein (specific activity) as mean ± SEM. In vitro maturation was performed with 2‐oxoglutarate (5, 10 and 20 mm) or hydroxymalonate (30, 60 and 100 mm) inhibitors of PFK and MDH, respectively. The PFK and MDH activities (U) remained constant during maturation. For PFK, the U were (2.48 ± 0.23) 10−5 and (2.54 ± 0.32) 10−5, and for MDH, the U were (4.72 ± 0.42) 10−5 and (4.38 ± 0.25) 10−5 for immature and in vitro matured COCs, respectively. The specific activities were significantly lower after IVM, for PFK (4.29 ± 0.48) 10−3 and (0.94 ± 0.12) 10−3, and for MDH (9.08 ± 0.93) 10−3 and (1.89 ± 0.10) 10−3 for immature and in vitro matured COCs, respectively. In vitro maturation percentages and enzymatic activity diminished with 20 mm 2‐oxoglutarate or 60 mm hydroxymalonate (p < 0.05). Viability was not affected by any concentration of the inhibitors evaluated. The U remained unchanged during IVM; however, the increase in the total protein content per COC provoked a decrease in the specific activity of both enzymes. Phosphofructokinase and MDH necessary for oocyte IVM would be already present in the immature oocyte. The presence of inhibitors of these enzymes impairs the meiotic maturation. Therefore, the participation of these enzymes in the energy metabolism of the porcine oocyte during IVM is confirmed in this study.